Application of lean six sigma in reducing the material consumption at wards in a selected healthcare unit. (2021) - Sakthivelmurugan, E.; Senthilkumar, G.; Tajdeen, A.; Manojkumar, S.
Abstract: Healthcare, as with any other service operation, requires systematic innovation efforts to remain competitive, cost-efficient, and up-to-date. Day by day the cost of medical care is escalating at a distressing and indefensible rate worldwide. The cost of medical care increases because of two factors such as the aging population and technological advances. Due to the technological and demographic developments of modern society, these two factors are greatly beyond the control. Additionally, the healthcare cost increases with unnecessary operational inefficiency and over usage of materials. Healthcare professionals have required more attention over the operational inefficiency. To improve quality, inefficiency is measured and changes can be implemented. These efforts give more compatible and better healthcare for a large percentage of the population. The objective of this project is to combine the principles of lean thinking and six sigma provides an effective framework to reduce the material consumption at wards and effective distribution of the materials from the stores to wards. In this context, information about the material consumed at different wards from different stores of healthcare was collected and the material distribution process was identified and root causes for the problems were identified in the analysis phase. It will be seen that problems will be eliminated in the improvement phase and it will be checked whether the process is in control or not in the control phase.